EKSPLORASI PERAN MOTIVASI DALAM MENINGKATKAN SEMANGAT BELAJAR BAHASA ARAB DI MADRASAH TSANAWIYAH NURUL HIDAYAH BLADO KULON - Mualim Wijaya; Malihatul Maulidiyah (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2021)
This paper aims to analyze and understand the problems in learning Arabic that result in low student enthusiasm for learning and the solutions and efforts made by Madrasah Tsanawiyah Nurul Hidayah Blado Kulon Probolinggo who apply the role of motivation in increasing enthusiasm for learning Arabic. This research uses a qualitative approach with a phenomenological type, with research located at Madrasah Tsanawiyah Nurul Hidayah Blado Kulon, researchers try to master the phenomena that occur in the madrasa through observation, interviews and documentation as information gathering techniques. Meanwhile, the presentation of information, reduction of information and drawing conclusions, including data analysis from this research. The results of the research show that how to increase the enthusiasm for learning Arabic which is carried out by Madrasah Tsanawiyah Nurul Hidayah Blado Kulon through motivation by providing encouragement in the form of guidance and counseling services, increasing the qualifications of Arabic language teachers and applying varied and communicative educational methods and strategies, using media attractive and communicative, giving rewards in the form of praise and comments to students, and creating competition and cooperation between students.